(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This study aimed to examine the impact of practicing psychological enlightenment techniques—including mindful meditation and mental awareness—on psychological stress, mental and physical recovery, and athletic performance among athletes in the Sultanate of Oman. The study adopted a descriptive-analytical approach. Data were collected through a specially designed questionnaire administered to a random sample of 24 athletes representing various sports. Statistical analyses included descriptive statistics, independent samples t-tests, and effect size calculations (Cohen’s d), using SPSS (version 27). Findings indicated that overall levels of psychological stress among participants were relatively low, while the perceived impact of psychological enlightenment on recovery and athletic performance ranged from moderate to high. Results further showed clear differences between athletes who regularly practiced mindful meditation and those who did not. Awareness of psychological enlightenment concepts, however, was generally limited, underscoring the need for broader educational and training efforts. Consistent with previous research, the study also revealed positive tendencies toward employing mindful and spiritual meditation to enhance athletic performance and reduce psychological pressure. The study concludes that integrating psychological enlightenment practices—particularly mindful and spiritual meditation—can play a significant role in reducing stress, improving recovery, and enhancing athletic performance. It recommends embedding regular meditation and awareness programs within sports training systems, strengthening the spiritual and faith-based dimensions of these programs, and implementing continuous workshops and monitoring mechanisms to assess their impact on athletes’ mental health and performance.